ANALISIS E-CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN YANG TERGABUNG DALAM SOCIALLY RESPONSIBLE INVESTMENT - Asyidiki, Ali (Jurnal Akuntansi AKUNESA, 2017)
This study aims to analyze the level of corporate social responsibility disclosure on their website on the company incorporated in socially responsible investment and different level of disclosure by sector. The type of this research is descriptive quantitative using secondary data of corporate social responsibility disclosure on their website with sample the company incorporated in socially responsible investment in Indonesia. Data were analyzed using descriptive statistical test and one way anova test. The results of this study suggest that the level of corporate social responsibility disclosure on their website is low and there is difference level of disclosure by sector.